Ergonomic risk assessment in DHM tools employing motion data - exposure calculation and comparison to epidemiological reference data. (2018) - Rhén, Ida-Märta; Forsman, Mikael; Örtengren, Roland; Högberg, Dan; Keyvani, Ali; Lämkull, Dan; Hanson, Lars
Digital human modelling (DHM) allows ergonomic risk assessment to be performed at early stages of design and development. Such assessment is typically based on observational methods, which do not take advantage of the potential of DHM tools to provide precise posture and motion data. This paper describes and illustrates an alternative assessment approach employing DHM tools, inspired by risk assessment based on direct measurements. A literature survey established a reference database of epidemiological associations between exposure and wrist-related disorders. This approach is illustrated by a DHM simulation of a car assembly task. Wrist posture and motion were simulated and compared to the database, predicting the prevalence of work-related musculoskeletal disorders on the basis of direct measurements.